2017
DOI: 10.1111/aor.12951
|View full text |Cite
|
Sign up to set email alerts
|

Veno‐Arterial Extracorporeal Membrane Oxygenation Support in Patients Undergoing Aortic Surgery

Abstract: Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is an option for mechanical support for patients with postcardiotomy cardiogenic shock (PCS). However, the use of VA-ECMO in patients suffering from aortic disease with PCS has not been greatly reported. This is a retrospective review of adult patients undergoing aortic surgery who received VA-ECMO support to treat refractory PCS from August 2009 to May 2016. A total of 36 patients who underwent aortic surgery with VA-ECMO support for refractory PCS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 21 publications
1
22
1
1
Order By: Relevance
“…authors concluded that ECLS implantation in acute aortic dissection is associated with extremely high mortality irrespective of when the intervention is performed. The mean duration of temporary mechanical support in our series was quite longer than that reported in previous studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Our analysis did not find a survival advantage in the most recent cohort.…”
contrasting
confidence: 65%
See 3 more Smart Citations
“…authors concluded that ECLS implantation in acute aortic dissection is associated with extremely high mortality irrespective of when the intervention is performed. The mean duration of temporary mechanical support in our series was quite longer than that reported in previous studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Our analysis did not find a survival advantage in the most recent cohort.…”
contrasting
confidence: 65%
“…24,25 In the present analysis, half of the study population showed signs of satisfactory myocardial recovery allowing for ECLS weaning but only 39% survived to hospital discharge. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In addition, a recent metaanalysis found that the pooled hospital survival after postcardiotomy ECLS was 36% (95% CI 31.5-40.8). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In addition, a recent metaanalysis found that the pooled hospital survival after postcardiotomy ECLS was 36% (95% CI 31.5-40.8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extra corporeal membrane oxygenation (ECMO) as a short‐term mechanical circulatory support has been widely used in patients with severe respiratory and/or circulatory failure . However, the rate of ECMO removal in PCS remains one of the lowest rates of all the indications varying from 58 to 67%, and the in‐hospital mortality varies from 50 to 74% Although the survival rate of ECMO support remains unsatisfactory with severe complications, such as bleeding, infection, end‐organ failures, lower limb ischemia, and thrombosis, ECMO is still a favorable technique treatment for PCS because of its easy and rapid applicability.…”
mentioning
confidence: 99%